TECHNOLOGIES FOR DEVELOPING COMMUNICATIVE SPEECH IN EARLY CHILDREN WITH SPEECH DELAY (International journal of artificial intelligence, 2026)
This article explores effective technologies for developing communicative activity in young children with speech development delay. The study analyzes innovative approaches aimed at fostering socio-communicative skills in this category of children, considering their specific needs. The paper discusses various pedagogical strategies, including interactive games, visual aids, and family collaboration. It emphasizes the significant role these technologies play in enhancing children's speech and communicative abilities. The findings provide valuable recommendations for practitioners and parents.